Organizational climate and its relationship with workplace violence in working women of Durango Mexico - Elizalde, Cristina; Figueroa, Geovani; Tortolero, Rosalío; Gómez, Ignacio (Gestionar: revista de empresa y gobierno, 2021)
As a general objective, the present investigation has to determine the correlation that exists between the organizational climate and labor violence from the perspective of working women from different productive sectors in the city of Durango, Mexico. For the compilation of information, the survey technique was used. The measurement instrument applied in the investigation consists of 82 reagents on a Likert scale (5, always; 4, sometimes; 3, some times; 2, many times and 1, never) distributed in two dimensions for the dependent variable. The labor violence and four for the independent variable organizational climate were applied to 153 women from different companies in November 2021. The design was used at the descriptive, correlational, and cross-sectional experimental levels in the investigation. It is concluded that there is evidence to affirm that the work climate presents a negative correlation with labor violence, obtaining a Spearman Rho coefficient of -.715.